2020
DOI: 10.1007/s12273-020-0743-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort in winter incorporating solar radiation effects at high altitudes and performance of improved passive solar design—Case of Lhasa

Abstract: The solar incidence on an indoor environment and its occupants has significant impacts on indoor thermal comfort. It can bring favorable passive solar heating and can result in undesired overheating (even in winter). This problem becomes more critical for high altitudes with high intensity of solar irradiance, while received limited attention. In this study, we explored the specific overheating and rising thermal discomfort in winter in Lhasa as a typical location of a cold climate at high altitudes. First, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Regarding closing the curtains, Huang and Kang (2021) concluded that an improvement was achieved in an indoor thermal environment when closing curtains by reducing overheating time to an average of 62.2%. Thus, the comfort time was increased accordingly.…”
Section: Shading Devices and Curtainsmentioning
confidence: 99%
“…Regarding closing the curtains, Huang and Kang (2021) concluded that an improvement was achieved in an indoor thermal environment when closing curtains by reducing overheating time to an average of 62.2%. Thus, the comfort time was increased accordingly.…”
Section: Shading Devices and Curtainsmentioning
confidence: 99%
“…While a large body of research has to some extent confirmed its effectiveness, most of these studies and applications are situated in plains or low-altitude areas, making them unsuitable for high-altitude regions. Furthermore, in indoor thermal environment research, scholars currently primarily employ field measurements (Huang and Kang, 2021) to study the impact of solar radiation on indoor thermal comfort and the occupants' response to solar radiation in the indoor environment. Surveybased studies (Thapa, 2020) propose new comfort zones for regions with similar cold climates based on the results of field surveys on thermal comfort.…”
Section: Introductionmentioning
confidence: 99%